(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Stepwells are architectural marvels unique to India. Historically, they sustained groundwater, moderated microclimates, and embedded water within cultural landscapes. Hydrological studies have shown that stepwells slow runoff and recharge aquifers; yet, today they are largely treated as heritage structures, sidelined from water policy. Given the climatic conditions of western India, restoring stepwells assumes renewed importance. Case evidence from Rajasthan’s johads (earthen check dams) and lake restoration initiatives in Bengaluru and Hyderabad demonstrates measurable aquifer gains when traditional systems are integrated at the catchment scale. The Sarkhej Roza–Makarba complex in Ahmedabad and the Adalaj Stepwell illustrate both the persistence of heritage value and the missed opportunity for hydrological reintegration, even though many stepwells have lost their functional identity as a result of urbanisation. Recasting heritage water systems as active infrastructure offers a pathway to climate-resilient urban water planning. Drawing on comparative case evidence, governance reviews, and secondary sources, this paper examines how traditional recharge systems can be repositioned within contemporary urban water management.